The Factors Related to Cadres’ Competency in Integrated Health Service Post during Pandemic - Ferry Fadzlul Rahman; Susilo Nur Aji Cokro Darsono; Sri Sunarti (Universitas Muhammadiyah Yogyakarta, 2023)
The competence of Posyandu (Integrated Service Post) cadres played a crucial role in response to the pandemic. They were responsible for raising awareness about COVID-19 and implementing preventive measures. The impact of their competence cannot be overstated and highlights the importance of investing in health worker training. This study aims to determine the factors related to the competence of Integrated Health Service Post cadres during the pandemic in the Samarinda Primary Healthcare working area. Observational research was employed with stratified random sampling, and primary data was collected from five Primary Healthcare in Samarinda. This study employed three steps to examine the effect of competency cadres: univariate analysis, bivariate analysis using the Spearman Rank test, and multivariate analysis with Multiple Linear Regression. The bivariate analysis results showed that supervision had a very strong correlation with the cadres’ competency, and social environment had a strong correlation with the cadres’ competency. At the same time, the organization had a moderate correlation with cadres’ competency. The multivariate test results showed that the social environment contributed 0.165 times to the competence of cadres, organizational support contributed 0.211 times in cadre competence, and supervision support contributed 0.652 times to cadre competence. It provides them with the necessary resources, training, and recognition for their work.